Effectiveness of the use of plant growth stimulants when creating Scots pine forest plantations in Kharkiv Forest Research Station - Даниленко, О. М.; Ющик, В. С.; Румянцев, М. Г. (Forestry and Forest Melioration, 2024)
Introduction In recent years, there has been a tendency to increase the cultivation of the containerized planting material of the main forest-forming species. Plant growth stimulants are used in many countries to intensify the growth of planting material for many tree and shrub species. However, the use of plant growth stimulants in forestry is fragmentary. This study aimed to assess the effect of plant growth stimulants on biometric characteristics, mass, and yield of standard containerized Scots pine planting material, as well as on mensuration indicators and viability of forest plantations established with such planting material in Kharkiv Forest Research Station. Materials and Methods Scots pine seedlings were grown in nursery conditions in agrotextile containers. During the growing season, two root or foliar feedings of seedlings were carried out with tested growth stimulants Tsyrkon, Hreynaktyv-S, Kornevin, Radifarm Plus, Aminostym, and Megafol in the norms recommended by the manufacturer. The effectiveness of the tested plant growth stimulants during the cultivation of one-year-old Scots pine seedlings was evaluated by biometric characteristics and the mass of the above-ground (trunks plus needles) and root (roots) parts in an air-dry state. Survivability in the first year of growth of forest plantations was determined as the ratio of the number of viable seedlings at the time of their accounting and those planted during the establishment of experimental plantations, expressed as a percentage. All preserved pine seedlings were measured according to treatments. Results The average height and the average diameter of one-year-old containerized pine seedlings were significantly greater in the treatments where root and foliar fertilizations with tested plant growth stimulants were applied. For example, the difference between the experimental treatments and the control was 21–52%, or 2.9–7.4 cm for the height and 7–20%, or 0.1–0.3 mm, for the root collar diameter. The largest mass of the above-ground part of an average Scots pine seedling in the air-dry state was determined in the Megafol treatment; it was 1.24 g and exceeded the control value by 46%. |The smallest mass of 0.99 g was detected in the Radifarm Plus treatment; the excess over the control was 16%. The largest mass of the root part of an average pine seedling was found in the Aminostym treatment; it was 0.62 g and exceeded the control by 59%. The smallest root mass of 0.49 g was recorded for the Radifarm Plus treatment with 26% excess over the control. The total weight of seedlings was 1.24–1.82 g. The proportion of standard seedlings in the control was 76%, while in the experimental treatments, it was 86–98%. Experimental one-year-old forest plantations were superior to the control by 4–30% in height, 1–18% in height increment, and 6–14% in root collar diameter. Conclusions Root and foliar treatment of seedlings with solutions of the tested growth stimulants Tsyrkon, Hreynaktyv-S, Kornevin, Radifarm Plus, Aminostym and Megafol in the conditions of the south-eastern part of the Left-Bank Forest-Steppe at the rates recommended by the manufacturer contributed to an increase in their biometric parameters and the mass of root and aboveground parts. The results showed both the higher mensuration parameters and survivability of one-year-old Scots pine forest plantations established using containerized planting material grown with the use of growth stimulants, as compared to the plantations established using both containerized planting material grown without growth stimulants and bare-root planting material. 4 Figs., 4 Tables, 25 Refs.